Experimental evaluation of an electromechanical artificial urinary sphincter in an animal model. (10th January 2013) - Valerio, Massimo; Jichlinski, Patrice; Dahlem, Roland; Tozzi, Piergiorgio; Mundy, Anthony R.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? The AMS 800 urinary control system is the gold standard for the treatment of urinary incontinence due to sphincter insufficiency. Despite excellent functional outcome and latest technological improvements, the revision rate remains significant. To overcome the shortcomings of the current device, we developed a modern electromechanical artificial urinary sphincter. The results demonstrated that this new sphincter is effective and well tolerated up to 3 months. This preliminary study represents a first step in the clinical application of novel technologies and an alternative compression mechanism to the urethra. Objectives To evaluate the effectiveness in continence achievement of a new electromechanical artificial urinary sphincter (emAUS) in an animal model. To assess urethral response and animal general response to short‐term and mid‐term activation of the emAUS. Materials and Methods The principle of the emAUS is electromechanical induction of alternating compression of successive segments of the urethra by a series of cuffs activated by artificial muscles. Between February 2009 and May 2010 the emAUS was implanted in 17 sheep divided into three groups. The first phase aimed to measure bladder leak point pressure during the activation of the device. The second and third phases aimed to assess tissue response to the presence of the device after 2–9 weeks and after 3 months respectively. Histopathological and immunohistochemistry evaluation of the urethra was performed. Results Bladder leak point pressure was measured at levels between 1091 ± 30.6 cmH2O and 1244.1 ± 99 cmH2O (mean ± standard deviation) depending on the number of cuffs used. At gross examination, the explanted urethra showed no sign of infection, atrophy or stricture. On microscopic examination no significant difference in structure was found between urethral structure surrounded by a cuff and control urethra. In the peripheral tissues, the implanted material elicited a chronic foreign body reaction. Apart from one case, specimens did not show significant presence of lymphocytes, polymorphonuclear leucocytes, necrosis or cell degeneration. Immunohistochemistry confirmed the absence of macrophages in the samples. Conclusions This animal study shows that the emAUS can provide continence. This new electronic controlled sequential alternating compression mechanism can avoid damage to urethral vascularity, at least up to 3 months after implantation. After this positive proof of concept, long‐term studies are needed before clinical application could be considered.